Tolerance of Ambiguity: A Variable in Client and Counsellor Pairing - Foote, Margaret; Davis, William L.; Marks, Stephen E. (Canadian Journal of Counselling and Psychotherapy, 2012)
This study examined the differential patterns of pairing1counsellors and clients on the personality variable Tolerance of Ambiguity(TA)and the effects on amount of counsellor talk during the interview,expressed client satisfaction, and the numbers of interviews attended by theclient. Counsellors with a high TA talked significantly more than counsellorswith a low TA and there was a significant interaction between differentialpairings of the counsellors and clients. Although there wasno significant difference in expressed satisfaction about the interviews,clients did return more often to counsellors with a high TA.